The Significance of Crescents on the Clinical Features and Outcomes of Primary Immunoglobin A Nephropathy - Du, Yongjing; Chen, Shasha; Wang, Fengping; Zhang, Ping; Liu, Mijia; Liu, Chi; Zhong, Xiang; Qin, Jianhua; Li, Guisen; Wang, Wei (Frontiers in Medicine, 2022)
Background It is still controversial whether the proportion of crescents below 50% can be an independent predictive risk factor for poor prognosis in IgAN patients. We reported the significance of different proportions of crescents on the clinical features and the cut-off value of crescents in predicting the occurrence of end-stage kidney disease (ESKD) in patients with IgAN. Methods We retrospectively analyzed biopsy-proven primary IgAN patients in Sichuan Provincial People’s Hospital from 2007 to 2019. The patients were divided into 5 groups on the basis of crescent proportion as follows: 0 (n = 647), < 10% (n = 221), 10 to 24% (n = 272), 25 to 49% (n = 80), and ≥50% (n = 22). The primary endpoint was defined as ESKD, and the secondary endpoint was the combined renal endpoint (≥50% reduction in eGFR or ESKD). A validation cohort of 346 patients were enrolled from Affiliated Hospital of Southwest Medical University. Cox regression model and Kaplan-Meier survival analysis were performed. Results A total of 1242 eligible patients with biopsy-proven IgAN were recorded in the database, compared with the non-crescent group, patients in the crescent group had lower levels of hemoglobin (Hb) and albumin (Alb), higher levels of blood urea nitrogen (BUN), 24h urinary protein and hematuria, a higher proportion of mesangial hypercellularity (M1), endocapillary hypercellularity (E1), segmental glomerulosclerosis (S1), and tubular atrophy/interstitial fibrosis (T1/T2) (p < 0.05). A higher crescent proportion was associated with lower levels of Hb, ALB, eGFR and serum IgG (p < 0.05), higher levels of SCr, BUN, increasing amounts of 24 h urinary protein, increasing proportion of M1 and E1, and increasing severity of interstitial inflammatory infiltration. During the median follow-up of 43 months (range 6-151), 63 individuals (7.0%) reached the primary outcome of ESKD and 99 patients (11.1%) reached the combined renal endpoint. 34(7.5%), 21 (13.3%), 24(12.2%), 14(21.5%) and 6(31.6%) patients reached the combined renal endpoint in the above five groups in crescents 0, <10%, 10∼24%, 25∼49% and ≥50%, respectively. A total of 274(62.6%) cases in the crescent group and 254 (55.7%) cases in the non-crescent group received immunosuppressive therapy. Multivariate Cox regression showed that crescents ≥50% was an independent risk factor for the progression of ESKD (p = 0.003) and crescents ≥25% was an independent risk factor for the combined renal endpoint(p < 0.001). The receiver operating characteristic curve showed that IgAN patients with crescents ≥43.7% had a higher risk of ESKD, even with immunosuppressants (Sensitivity = 75.7%,specificity = 89.6%,p < 0.001). This discovery cohort and the validation cohort further confirmed that patients with crescents <43.7% had better renal prognosis than those with crescents ≥43.7% in the whole group and those with immunosuppressants (p < 0.001). Conclusion IgAN patients with crescents had more severe clinicopathological features and poorer prognosis. Crescents ≥50% was an independent risk factor for the progression of ESKD and crescents ≥25% was an independent risk factor for ≥50% reduction in eGFR or ESKD in treated and untreated IgAN patients. Crescents ≥43.7% was an independent risk factor for ESKD in those with immunosuppressants.